The Association Between Screen Time Duration and Language Development Among Children Aged 2–5 Years: A Cross-Sectional Study - Maria Katharina Nini Papang; Christina Olly Lada; Audrey Gracelia Riwu; Regina Marvina Hutasoit (Universitas Muhammadiyah Sidoarjo, 2026)
Language development is a crucial aspect of a child’s growth and development. A child’s language development can be influenced by the duration of screen time, particularly during the “golden age” of 2–5 years. This study aims to determine whether there is a relationship between screen time duration and language development in children aged 2–5 years. This study was conducted in the service areas of the Sikumana Community Health Center and the Tarus Community Health Center with a sample size of 60 participants using a sequential sampling method. The research method employed was quantitative with a cross-sectional design. Based on the results of the chi-square test, a p-value of 0.02 was obtained, indicating that there is a relationship between screen time duration and language development in children aged 2–5 years.